The nature of behavioural correlates of healthy ageing: a twin study of lifestyle in mid to late life - McGue, Matt (Oxford University Press, 2014)
Background With the greying of the industrialized world has come increased interest in identifying the modifiable lifestyle factors that promote healthy and successful ageing. Whereas many of the behavioural correlates of late-life morbidity and mortality have been identified, relatively little is known about the origins of individual differences in these factors. Methods A sample of 12 714 twins, including both members of 3806 pairs of known zygosity, ascertained through the Danish Twin Registry and aged 40 to 80 years, completed a self-report assessment of six lifestyle factors associated with ageing: smoking, drinking, diet and physical, social and intellectual activities. Standard biometric methods were used to analyse the twin data and determine the extent to which individual differences in each of the lifestyle factors are heritable. Results For each of the six lifestyle factors, the estimate of heritability ranged from 32% (95% CI: 19–42%) for the diet scale to 69% (62–72%) for the smoking measure. Biometric estimates of the contribution of the twins’ common rearing environment were uniformly small (≤6%). There was little evidence that standardized biometric estimates varied by gender or age. Conclusions Individuals likely construct lifestyles in part to complement and reinforce underlying genetically influenced dispositions and talents. The heritable nature of lifestyle factors implies that the behavioural and genetic contributors to ageing processes are not necessarily conceptually distinct but rather reflect the complexity of gene-environment interplay in ageing.